2023
DOI: 10.3390/su15076212
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Moisture Content and Dry Density on the Compressibility of Disturbed Loess: A Case Study in Yan’an City, China

Abstract: Loess is a kind of soil that experiences a long period of deposition, and it is relatively stable under natural conditions. However, in the process of engineering construction in loess areas, the original soil structures of the loess are destroyed, inducing changes in the composition and water content in the loess. These changes may cause different environmental and engineering geologic problems. To reveal the engineering properties of disturbed losses in the Chinese Loess Plateau, the physical properties of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…These vulnerabilities often lead to various natural disasters, such as loess landslides, collapses, ground subsidence, and soil erosion [10]. In recent years, due to the increase in human activities [11,12] and environmental degradation, these disasters have happened frequently, severely impacting socioeconomic development and the safety of people's lives and property [13][14][15]. As a result, they have gained significant a ention.…”
Section: Introductionmentioning
confidence: 99%
“…These vulnerabilities often lead to various natural disasters, such as loess landslides, collapses, ground subsidence, and soil erosion [10]. In recent years, due to the increase in human activities [11,12] and environmental degradation, these disasters have happened frequently, severely impacting socioeconomic development and the safety of people's lives and property [13][14][15]. As a result, they have gained significant a ention.…”
Section: Introductionmentioning
confidence: 99%
“…The collapsibility of loess in the Loess Plateau poses unique challenges for the sustainable operation of infrastructure. These challenges make resource development and the continuous progress of various projects in the Loess region more difficult [6]. As the western development progresses, engineering endeavors in loess regions are bound to encounter collapsibility issues, posing significant challenges to site selection and the safe operation of constructed facilities [7].…”
Section: Introductionmentioning
confidence: 99%
“…Loess is a kind of silty clay with large pores, incomplete consolidation, and collapsibility. Based on a large number of studies [56][57][58][59][60], undisturbed loess is observed to have the following remarkable properties:…”
Section: Introductionmentioning
confidence: 99%